PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI KERJA TERHADAP KINERJA PENYULUH KELUARGA BERENCANA (PKB) PADA BADAN KELUARGA BERENCANA DAN PEMBERDAYAAN PEREMPUAN (BKBPP) KABUPATEN KARAWANG - Sofiyanti, Neneng; Kristamtomo Putra, R. Aditya (Jurnal Manajemen dan Bisnis Kreatif, 2017)
ABSTRACT The result of preliminary studies was found that Penyuluh Keluarga Berencana (PKB) Performance is not yet optimal. Of the many factors that cause is found, Career Development and work motivation is the most dominant factor of influence. Therefore the formulated problem include : how career development, work motivation, and Penyuluh Keluarga Berencana performance. How was significant on career development and work motivation to Penyuluh Keluarga Berencana performance at BKBPP Sub-Province of Karawang by partial and simultan. . The research of target is obtaining empiric evidence and finding clarity of phenomenon and also conclusion about the influence of career development and work motivation to Penyuluh Keluarga Berencana performance at BKBPP Sub-Province of Karawang. The research method used is descriptive survey and explanatory survey. The sampling technique was used sensus method. Data analysis techniques is to expose each variable we,it used range scale. Data analysis technique used correlation analysis technique variables and Path Analysis Technique, to expose the influence of career development and work motivation. The conclusion from the examination that : 1. Career Development at BKBPP Sub-Province of Karawang is quite good. 2. Work Motivation at BKBPP Sub-Province of Karawang is high. 3. Performance of Penyuluh Keluarga Berencana at BKBPP Sub-Province of Karawang is quite high. 4. Career development Influence directly to Performance of Penyuluh Keluarga Berencana at BKBPP Sub-Province of Karawang 5. Work motivation Influence directly to Performance of Penyuluh Keluarga Berencana at BKBPP Sub-Province of Karawang. 6. career development and work motivation Simultaneously influence to Performance of Penyuluh Keluarga Berencana at BKBPP Sub-Province of Karawang. Keywords : Career Development, Work Motivation, Performance of Penyuluh Keluarga Berencana